RIPK1 deficiency prevents thymic NK1.1 expression and subsequent iNKT cell development - Hägglöf, Thomas; Parthasarathy, Raksha; Liendo, Nathaniel; Dudley, Elizabeth A.; Leadbetter, Elizabeth A. (Frontiers in Immunology, 2023)
Receptor Interacting Protein Kinase 1 (RIPK1) and caspase-8 (Casp8) jointly orchestrate apoptosis, a key mechanism for eliminating developing T cells which have autoreactive or improperly arranged T cell receptors. Mutations in the scaffolding domain of Ripk1 gene have been identified in humans with autoinflammatory diseases like Cleavage Resistant RIPK1 Induced Autoinflammatory (CRIA) and Inflammatory Bowel Disease. RIPK1 protein also contributes to conventional T cell differentiation and peripheral T cell homeostasis through its scaffolding domain in a cell death independent context. Ripk1 deficient mice do not survive beyond birth, so we have studied the function of this kinase in vivo against a backdrop Ripk3 and Casp8 deficiency which allows the mice to survive to adulthood. These studies reveal a key role for RIPK1 in mediating NK1.1 expression, including on thymic iNKT cells, which is a key requirement for thymic stage 2 to stage 3 transition as well as iNKT cell precursor development. These results are consistent with RIPK1 mediating responses to TcR engagement, which influence NK1.1 expression and iNKT cell thymic development. We also used in vivo and in vitro stimulation assays to confirm a role for both Casp8 and RIPK1 in mediating iNKT cytokine effector responses. Finally, we also noted expanded and hyperactivated iNKT follicular helper (iNKTFH) cells in both DKO (Casp8-, Ripk3-deficient) and TKO mice (Ripk1-, Casp8-, Ripk3-deficient). Thus, while RIPK1 and Casp8 jointly facilitate iNKT effector function, RIPK1 uniquely influenced thymic iNKT cell development most likely by regulating molecular responses to T cell receptor engagement. iNKT developmental and functional aberrances were not evident in mice expressing a kinase-dead version of RIPK1 (RIPK1kd), indicating that the scaffolding function of this protein exerts the critical regulation of iNKT cells. Our findings suggest that small molecule inhibitors of RIPK1 could be used to regulate iNKT cell development and effector function to alleviate autoinflammatory conditions in humans.